KEPATUHAN MINUM OBAT PADA PASIEN SKIZOFRENIA DENGAN GANGGUAN PERSEPSI SENSORI HALUSINASI PENDENGARAN - Amaliah, Siti Lia; Wungu, Aprilla Dewi Kencana (MIDWINERSLION Jurnal Kesehatan STIKes Buleleng, 2024)
Introduction: Hallucinations are a false stimulus that can only be felt by the sufferer and cannot be felt by other people. The purpose of writing this scientific paper is to describe the implementation of nursing in implementing medication adherence in schizophrenic patients with auditory hallucination sensory perception disorders. Method: The type of research used is descriptive type. In collecting scientific writing data using interview and observation methods. In this writing, one of the respondents who was diagnosed with hallucinatory sensory perception disorder was taken. The research instrument used nursing care sheets and observation sheets. The research results obtained at the time of assessment, obtained nursing problems sensory perception disorders auditory hallucinations. Result: Result in this study after implementing the implementation of taking medication for 3 days, clients can control hallucinations and there is a decrease in signs and symptoms of hallucinations. Conclusion: The conclusion of the action of implementing medication adherence is proven to be effective in reducing signs and symptoms of hallucinations.